Hubungan antara penguasaan kalimat efektif dan minat membaca dengan keterampilan menulis karangan narasi peserta didik kelas v sekolah dasar - Qibtiah, Maryatul; Slamet, Slamet (Didaktika Dwija Indria, 2026)
This study aims to (1) determine the correlation between mastery of effective sentences and narrative writing skills; (2) determine the correlation between reading interest and narrative writing skills; and (3) investigate the correlation between the mastery of effective sentences and reading interest with the narrative writing skills. The research employed a quantitative approach with a correlational design, involving 97 fifth-grade students from public elementary schools in Laweyan District during the 2024/2025 academic year, selected using cluster random sampling. Data were collected through a writing test to assess narrative writing skills, a multiple-choice test for mastery of effective sentences, and a questionnaire to measure reading interest. The data were analyzed using simple and multiple correlation techniques. The results showed significant positive correlation: (1) between mastery of effective sentences and narrative writing skills (; (2) between reading interest and narrative writing skills with ; and (3) simultaneously between both variables and narrative writing skills (. These findings suggest that both variables positively contribute to students’ writing proficiency. Instructional strategies should emphasize sentences construction and promote reading habits to improve students’ narrative writing skills.